Direct electrochemical detection of individual collisions between magnetic microbead/silver nanoparticle conjugates and a magnetized ultramicroelectrode. Issue 11 (29th July 2015) - Yoo, Jason J.; Kim, Joohoon; Crooks, Richard M.
Abstract : Magnetic fields and silver nanoparticles increase the frequency and current signature of collisions between individual particles and electrode surfaces. Abstract : Here, we report on the electrochemical detection of individual collisions between a conjugate consisting of silver nanoparticles (AgNPs) linked to conductive magnetic microbeads (cMμBs) via DNA hybridization and a magnetized electrode. The important result is that the presence of the magnetic field increases the flux of the conjugate to the electrode surface, and this in turn increases the collision frequency and improves the limit of detection (20 aM). In addition, the magnitude of the charge associated with the collisions is greatly enhanced in the presence of the magnetic field. The integration of DNA into the detection protocol potentially provides a means for using electrochemical collisions for applications in biological and chemical sensing.